MODEL PEMBELAJARAN IPA DENGAN ALAT PERAGA SEDERHANA UNTUK MENINGKATKAN PEMAHAMAN DAN KREATIVITAS SISWA DI MTS MAâARIF CIKERUH, JATINANGOR - Budiman, Arif Agung; Inggriani, Astri Sherly; Prasetyo, Yuli Agung; Fauziah, Nisrina; Septiana, Nurfina (Dharmakarya, 2016)
ABSTRACTPracticum is a teaching strategy that is used to describe the learning materials. Props is one of the practical tools needed to assist in the learning activities. The purpose of this activity is to create props in enhancing the understanding and creativity of students in science subjects in MTs Maâarif Cikeruh, Jatinangor. The event begins socialization to MTs Maâarif Cikeruh Jatinangor, followed by the preparation of tools and materials to be used, then conducted the experiment installation of equipment before it is demonstrated to the students. Before making props, students are given a pre-test and explanation of theories related to props are made. Props are made include simple auksanometer, simple bioreactor, simple distillation apparatus, means of fermentation, miniature hydraulic pump, a water filter is simple, natural ph indicator, colored fountains, and sugar snake. Implementation of the activities take place every two weeks for four months from March to June 2016 and will be associated with the ongoing evaluation and monitoring activities. Evaluation and monitoring includes affective, psychomotor, and cognitive. Rate affective and psychomotor aspects conveniently indicates the criteria very well, while the students do with the cognitive aspects of the pre-test and post-test each meeting. The average value of the pre-test is 40.75, after a practicum conducted post-test with the average value is 74.125. Thus concluded practicum enhance students understanding of 33.375.Keywords: simple props, science, junior high school students